Spiralling whitefly, Aleurodicus dispersus in Nigeria - Akinlosotu, T.A.; Jackai, L.E.N.; Ntonifor, N.; Hassan, A.; Agyakwa, C.W.; Odebiyi, J.; Akingbohungbe, A.E.; Rossel, H.W. (1994)
The aleyrodid Aleurodicus dispersus is reported from Nigeria. The first observation was made on cassava in early 1992 at several locations in Ibadan. A survey carried out in January 1993 revealed that several genera, many of them important food and ornamental crops, are food plants of the insect.